Effect of Collaborative Strategic Reading (CSR)-Aided Instruction on Students’ Critical Reading in Post-Covid 19 Pandemic - Kamarudin . (Cordova Journal : languages and culture studies, 2021)
There have been numerous studies on collaborative strategic reading (CSR) in English language instruction; however, only a few of them have demonstrated its usefulness in critical reading comprehension. As a result, the purpose of this quasi-experimental study was to see how it affected students' critical reading skills when used as a teaching method in one of Lombok's private schools. There were 40 students in total, divided into two groups, one experimental and one control. To assess students' critical reading achievement, both groups were given a pre-test and a post-test, which were analyzed using the t-test method. By t-test = 2.169 and t-table = 1.679, the statistical evidence demonstrated that the experimental group considerably beat their counterparts in the control group in terms of critical reading comprehension. As a result, CSR was very helpful in cultivating students' critical reading comprehension.